Activity and stability trends of perovskite oxides for oxygen evolution catalysis at neutral pH1. Issue 35 (21st September 2015) - Han, Binghong; Risch, Marcel; Lee, Yueh-Lin; Ling, Chen; Jia, Hongfei; Shao-Horn, Yang
<x xml:space="preserve">Abstract</x> Perovskite oxides (ABO3) have been studied extensively to promote the kinetics of oxygen evolution reaction (OER) at neutral pH. The same activity descriptors apply in alkaline and neutral media. Yet, stability is a greater challenge in neutral media.